2015
DOI: 10.1134/s0032945215020046
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal condition, sperm motility, and initial stages of embryonic development in freckled goatfish Upeneus tragula (Mullidae)

Abstract: Development of sex cells, sperm motility, and initial stages of embryonic development are described in a tropical representative of the family Mullidae, freckled goatfish Upeneus tragula, from the coastal zone of Vietnam. In Nha Trang Bay, the gonads in the majority of sexually mature females are at IV, IV-V, and VI-IV maturity stages over the entire year, and the type of oogenesis is continuous. Anomalous structure of oocytes is registered in 15% of investigated females. In Ha Long Bay, the gonads of almost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…These results were in agreement with the previous studies that recorded by (El-Drawany, 2012) for U. moluccensis in Elkhoms coast of Libya; (Ismen, 2005) in Üskenderun Bay, the Eastern Mediterranean; (Torcu and mater, 2000) in the Fethiye and Mersin Gulfs; Ozvarol et al, (2010) in the Gulf of Antalya and Kaya et al, (1999) in south Aegean. Emel'yanovaa et al, (2015) concluded that goatfishes are pelagic spawning and the maturity stages progression with the time of spawning in summer. Cole et al, (2009) concluded that the spawning period of the yellow stripe goatfish (M. flavolineatus) and the yellow fin (M. vanicolensis) was from April through July, as they have an extended spawning season.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in agreement with the previous studies that recorded by (El-Drawany, 2012) for U. moluccensis in Elkhoms coast of Libya; (Ismen, 2005) in Üskenderun Bay, the Eastern Mediterranean; (Torcu and mater, 2000) in the Fethiye and Mersin Gulfs; Ozvarol et al, (2010) in the Gulf of Antalya and Kaya et al, (1999) in south Aegean. Emel'yanovaa et al, (2015) concluded that goatfishes are pelagic spawning and the maturity stages progression with the time of spawning in summer. Cole et al, (2009) concluded that the spawning period of the yellow stripe goatfish (M. flavolineatus) and the yellow fin (M. vanicolensis) was from April through July, as they have an extended spawning season.…”
Section: Discussionmentioning
confidence: 99%